Significance of Haldi (turmeric) in a wedding - Mumbai Archive Project Team (Jio Institute, 2024)
In Hindu culture, turmeric is considered auspicious and is believed to have purifying properties. Applying turmeric paste to the bride's skin is believed to cleanse her body of impurities, preparing her for the sacred union of marriage.